2022
DOI: 10.14245/ns.2143116.558
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve and Complications of Unilateral Biportal Endoscopy: Cumulative Sum and Risk-Adjusted Cumulative Sum Analysis

Abstract: Objective:The purpose of this study was to investigate the learning curve and complications of unilateral biportal endoscopy (UBE) in the treatment of lumbar disc herniation (LDH) and lumbar spinal stenosis (LSS).Methods: This was a retrospective cohort analysis of 197 consecutive patients who received UBE unilateral laminotomy bilateral decompression (UBE-ULBD) or lumbar discectomy (UBE-LD) surgery, including 107 males and 90 females with an average age of 64.83 ± 14.29 years. Cumulative sum (CUSUM) and risk-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Therefore, the learning curve of UBE is relatively flat and short. Xu demonstrated that the learning curve for mastering UBE is 54 cases ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the learning curve of UBE is relatively flat and short. Xu demonstrated that the learning curve for mastering UBE is 54 cases ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the surgical complication rate was similar between ULIF and conventional procedures (ULIF vs. MI-TLIF, 6.9 vs. 6.7%; ULIF vs. PLIF, 6.8% vs. 5.1%), the slightly higher incidence of dural tear in the ULIF group should be noted (ULIF vs. MI-TLIF, 4.8% vs. 2.1%; ULIF vs. PLIF, 4.7% vs. 2.8%). Therefore, ULIF is recommended for surgeons who have performed at least 54 cases of biportal endoscopic decompression ( 70 ). Another complication was the epidural hematoma, most likely due to oozing from the bone trapped under the intact posterior tension band, which usually could be resolved by itself ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, 7 articles were included in the meta-analysis, with a total sample size of 760 cases, including 398 cases in the UBE group and 362 cases in the control group. The basic characteristics of the included literature are shown in Table 1 (14)(15)(16)(17)(18)(19)(20).…”
Section: Basic Characteristics Of the Included Studiesmentioning
confidence: 99%